Managing your research data and documentation - Berenson, Kathy R. (Concise guides to conducting behavioral, health, and social science research series., 2017)
"In the behavioral sciences today, there is increasing emphasis on transparency, and the need for research studies to be made replicable. In this book, Kathy R. Berenson presents a straightforward approach to managing and documenting one's data so that other researchers can repeat the study. While data management may seem intimidating to new researchers, this guide shows how easy it can (and should) be. The first chapter presents a basic structure of folders and subfolders for organizing data files, and then each subsequent chapter delves into details for a specific folder. Step by step, readers learn to label and archive different kinds of project documents and data files, including original, processed, and working data. Readers also learn to write command codes showing exactly how the original data are analyzed. Examples illustrate how to document the most common types of research, and since major research funders now require recipients to meet strict data handling standards, this resource will foster a vital career skill for students."--